THE ETHICAL SUBJECT AND ITS RESPONSIBILITY. - FRUNZĂ, SANDU (Journal for the Study of Religions & Ideologies)
We are setting off here on a quest for the ethical subject and the metamorphoses of its positioning in the context of subject assertion and intersubjectivity development in postmodern ethics. Our main concern is with the way in which the ethical subject (agent) may be identified and delineated in the time of lay ethics and postmodern human condition. To do so, we firstly looked at how religious traditions provided firm grounds for identity and ethical subject assertion by integrating it into a dynamic of the divine and human having a special force to transfigure the person. We have relied in this sense on the use of the Cosmic Tree symbolism as a centre organizing the symbolic universe of human being. Secondly, our analyses aimed for the ultimate support of human being, that enables our approach of the moral subject as operating within the responsibility to oneself and to the multiple forms that alterity may take. We therefore begin with the premise that understanding self-esteem mechanisms may be the starting point in a harmonious construction of the self. Finally, we identify the moral self as the fundamental structure in the ethical reconstruction of the human being, understood as subject of ethical creation and moral perfection.